Physicochemical characterization of starch based films - Bertuzzi, Maria Alejandra (2007)
In the present study, high amylose corn starch (HACS) based films were obtained with a low temperature method consisted on reduce gelatinization temperature by an alkaline pretreatment of starch. Effects of film composition and preparation method on film properties were investigated to identify HACS film elaboration conditions to improve film properties. Rheological behavior of film-forming solutions is reported. Films were physical and chemically characterized through film solubility in water, water sorption isotherms, opacity and crystallinity of films. Film forming suspensions show pseudoplastic and thixotropic behavior. Apparent viscosity of film forming gel increases exponentially with HACS concentration and Arrhenius law adequately represents variation with temperature. Alkaline treatment time of HACS previous to gelatinization, also affects film properties. It was found that film solubility and opacity decrease while crystallinity increases although it reaches an asymptotic value after treatment time of 60 min. Above 30% of glycerol, an increase in plasticizer content conduces to a looser network, as a result film opacity and water sorption increase. © 2007 Elsevier Ltd. All rights reserved.